Correlation Between Cyberbullying Victimization And Self-Harm Behavior In Adolescents In Surakarta - Fitri Rahma Basriyah Amin (Green Publisher, 2025)
This study aimed to examine the relationship between cyberbullying victimisation and self-harm behaviour among adolescents in Surakarta, Indonesia. Cyberbullying victimization, as a form of online aggression, has been linked to various adverse psychological outcomes, including self-harm. Methods: A quantitative research design was employed, using cluster sampling to select participants. The sample consisted of 803 adolescents aged 12-18 years. Data were collected using the Self-Harm Behavior Scale (? = 0.841) and the Cyberbullying Victimization Scale (? = 0.932). A simple linear regression analysis was conducted to test the hypothesis. Results: The study revealed a significant positive relationship between cyberbullying victimization and self-harm behavior (F = 12.256, p = 0.000). Cyberbullying victimization had a moderate correlation with self- harm (R = 0.4) and accounted for 15.7% of the variance in self-harm behavior (R² = 0.157). Conclusions: Cyberbullying victimization is significantly associated with self-harm behavior among adolescents in Surakarta. These findings highlight the need for targeted interventions to reduce cyberbullying and support adolescents at risk of self-harm. The study contributes to the literature on adolescent mental health and provides a basis for future research and policy recommendations.